Analysis of Parking Lot Needs at Cibinong Regional General Hospital - Syaiful, Syaiful; Suparman, Awwad; Wardhani, Asri Kusuma (ASTONJADRO, 2025)
Cibinong Regional General Hospital is one of the centers of activity that is widely visited by people from the Cibinong area and from outside Cibinong for treatment or for one reason or another. Cibinong Regional General Hospital is also inseparable from parking problems that can interfere with the level of comfort in the service process provided by the hospital. The increasing number of patients certainly has an impact on increasing vehicle ownership which causes an increase in parking needs. In solving these problems, this study aims to determine the characteristics of parking, capacity and parking space needs that occur at this time. Based on the results of survey data conducted on the Cibinong Regional Hospital parking lot for 7 (seven) days on Monday, December 11, 2023 to Sunday, December 17, 2023, the parking capacity available for motorbikes is 851.145m2 with a capacity of 304 SRP while the parking area provided for passenger cars is 3628.55m2 with a capacity of 86 SRP. The data obtained from the maximum parking volume per day for motorcycles occurred on Sunday amounting to 481 vehicles while for passenger cars it occurred on Sunday amounting to 175 vehicles, with the maximum accumulation for motorcycles on Tuesday amounting to 318 vehicles, while the maximum parking accumulation for cars on Saturday amounting to 92 vehicles, with a time span of parking duration for motorcycles obtained, namely a maximum duration of 9 hours 22 minutes, an average duration of 3 hours 40 minutes, a minimum duration of 6 minutes while the parking duration for passenger cars obtained, namely a maximum duration of 8 hours 5 minutes, an average duration of 3 hours 11 minutes, a minimum duration of 14 minutes. With the turnover parking for motorcycles obtained, namely a maximum of 158.22% while for passenger cars obtained a maximum of 203.49%, and the parking index for motorcycles obtained a maximum of 104.61% while for passenger cars obtained a maximum of 106.98%. This shows that the parking performance of motorcycles and cars is quite high by looking at the parking index exceeding 100%. Thus, the parking capacity for motorcycles and passenger cars available is not sufficient to accommodate motorcycles and passenger cars in the Cibinong Regional Public Hospital parking lot.